Study of n-alkylamine Intercalated Layered Perovskite-Like Niobates HCa2Nb3O10 as Photocatalysts for Hydrogen Production From an Aqueous Solution of Methanol - Voytovich, Vladimir V.; Kurnosenko, Sergei A.; Silyukov, Oleg I.; Rodionov, Ivan A.; Minich, Iana A.; Zvereva, Irina A. (Frontiers in Chemistry, 2020)
A series of hybrid niobates HCa2Nb3O10×RNH2, containing n-alkylamines (R = Me, Et, Pr, Bu, Hx, Oc) intercalated into the interlayer space, has been thoroughly studied concerning the photocatalytic hydrogen production from a model aqueous solution of methanol for the first time. All the hybrid photocatalysts were synthesized by the conventional ceramic technique followed by protonation and intercalation of n-alkylamines. The products were characterized using XRD, Raman, IR and diffuse reflectance spectroscopy, TGA, CHN-analysis and SEM. Photocatalytic measurements were conducted according to an advanced scheme taking into account possible changes in the photocatalyst concentration because of sedimentation, pH shifts and exfoliation of the samples into nanoplatelets. Special attention was also paid to the feasible improvement of the photocatalytic activity of the samples via their modification with Pt nanoparticles as a cocatalyst. In the series of amine derivatives, the highest rate of hydrogen generation was demonstrated by the Pt-loaded HCa2Nb3O10×BuNH2 reaching apparent quantum efficiency of 13% in the 220–340 nm range. The initial HCa2Nb3O10 showed comparable efficiency of 8.3% that is greater than for other amine derivatives. It was demonstrated that for the investigated samples the photocatalytic activity correlates with their ability of water intercalation.